A transformação semiótica da filosofia transcendental clássica - Rodrigues, Adriano Messias (2011)
This paper is on the theme of the transformation of Philosophy held by Karl-Otto Apel from the radicalization of linguistic and pragmatic twist by showing the ineradicable nature of linguistic praxis for the general knowledge by means of a strict self-reflexive attitude of thought along with the language on the assumptions of the irrefutable argument as such. To this end, we investigate the main theoretical features for a semiotic transformation of the classic transcendental philosophy, especially the three-dimensional Peircean semiotics. Moreover, the objective is to demonstrate that a self-reflexive philosophy is able to justify scientific propositions as well as ethical and moral standards. The end of this research points to the relevance of the proposal of Apel when he faces the challenge imposed by the “historicization” of the thought, not through an “untranscendentalizing” posture towards reason but in the way of an eventual non-metaphysical foundation – beyond the social and historical contingencies, thereby reflecting what is specific of the philosophical reflection as the themes of the universal principles of our thinking and acting.